2021
DOI: 10.1016/j.coph.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal manifestations and SARS-CoV-2 infection

Abstract: Since COVID-19 occurrence in late 2019, intense research efforts on an unprecedented scale have focused on the study of SARS CoV-2 entry mechanisms and clinical presentations. As for other coronaviruses, SARS-CoV-2 presents with extra-respiratory clinical manifestations like diarrhea, nausea, vomiting and abdominal pain which highlight that the gastrointestinal (GI) system as another viral target along with the typical presentations of COVID-19 which is characterized primarily by respiratory symptoms. The dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In particular, the most common symptoms reported in both age groups are in the order of frequency diarrhea, nausea/vomiting and abdominal pain. systematic review and meta-analysis 5601 -diarrhea (10.4%) -nausea/vomit (7.7%) -abdominal pain (6.9%) / Furthermore, in children, the presence of gastrointestinal symptoms was significantly associated with a severe clinical course, while, in adults, the data are discordant in this regard [11,[45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the most common symptoms reported in both age groups are in the order of frequency diarrhea, nausea/vomiting and abdominal pain. systematic review and meta-analysis 5601 -diarrhea (10.4%) -nausea/vomit (7.7%) -abdominal pain (6.9%) / Furthermore, in children, the presence of gastrointestinal symptoms was significantly associated with a severe clinical course, while, in adults, the data are discordant in this regard [11,[45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in children, the presence of gastrointestinal symptoms was significantly associated with a severe clinical course, while, in adults, the data are discordant in this regard [ 11 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…While COVID‐19 is commonly considered a respiratory illness, 17%–53% of patients report GI symptoms (commonly abdominal pain, diarrhoea, nausea and vomiting), and in 10% of cases these are in the absence of respiratory symptoms 1 . The SARS‐CoV‐2 viral entry binding site is angiotensin converting enzyme 2, which is most highly expressed on the apical membrane of enterocytes at the small bowel brush border 4 . Additionally, SARS‐CoV‐2 RNA has been demonstrated in sloughed epithelial cells within COVID‐19 patient faecal samples 2,4 .…”
Section: Figmentioning
confidence: 99%
“…2,4 GI mucosal inflammation and ulceration have been associated with COVID-19, with several pathophysiologic mechanisms proposed, including 'stress' ulceration as well as direct enterocyte infection. 1,4 Stress ulceration is a multifactorial condition in which the physiologic stress of critical illness causes GI mucosal hypoperfusion and de novo ulceration, or worsening of existing ulcerative disease. 5 However, a recent cohort study of COVID-19 inpatients that required endoscopy for any indication found that 50% had GI mucosal damage, and multivariate analysis could not attribute this to severity of illness alone.…”
mentioning
confidence: 99%
“…While COVID-19 infection is primarily a respiratory illness, patients often experience extrapulmonary symptoms. Gastrointestinal (GI) symptoms including diarrhea, nausea, vomiting, and abdominal pain are frequently reported [3] , [4] , [5] , [6] . Additionally, bowel wall abnormalities were observed in 31 % of computed tomography (CT) scans performed in COVID-19 patients [7] .…”
Section: Introductionmentioning
confidence: 99%